PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PADA TIM FUTSAL PUTRA HARAPAN BARU STREET TEMBILAHAN - Muhammad Lutvi; Agus Sulastio; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to determine the effect of interval training on the endurance of the Harapan Baru Street Tembilahan futsal team. posttest design. In this research design, it begins with the first step taken is to do a pretest, namely the balcony test to measure the athlete's ability before being given treatment. Then the sample was given treatment, namely interval training exercises for 16 meetings, then a final test was carried out, namely the posttest with the Balke test to see if there was an increase after being given treatment. This research was conducted from January to February 2023 at the Harapan Baru futsal field, Tembilahan Street. The sampling technique is saturated sampling because the population is relatively small, less than 30 people, or the researcher wants to make generalizations with very small errors. Then the sample in this study was set as many as 10 people. Based on the data analysis and discussion that has been described previously, it can be concluded that interval training exercises have an effect on endurance in the new hope street tembilahan futsal team with an average pre-test result of only 37.41, while the post-test results reach 42.50 with an increase of 5.09%. It turns out that the average size after being given interval training is increasing, this is in accordance with the results of the hypothesis test t count 6.952 > t table 1.833 meaning the hypothesis is accepted.Key Words: Interval Training, Endurance